Variants of Transient Receptor Potential Melastatin Member 4 in Childhood Atrioventricular Block. Issue 5 (20th May 2016) - Syam, Ninda; Chatel, Stéphanie; Ozhathil, Lijo Cherian; Sottas, Valentin; Rougier, Jean‐Sébastien; Baruteau, Alban; Baron, Estelle; Amarouch, Mohamed‐Yassine; Daumy, Xavier; Probst, Vincent; Schott, Jean‐Jacques; Abriel, Hugues
Abstract : Background: Transient receptor potential melastatin member 4 (TRPM4) is a nonselective cation channel. TRPM4 mutations have been linked to cardiac conduction disease and Brugada syndrome. The mechanisms underlying TRPM4‐dependent conduction slowing are not fully understood. The aim of this study was to characterize TRPM4 genetic variants found in patients with congenital or childhood atrioventricular block. Methods and Results: Ninety‐one patients with congenital or childhood atrioventricular block were screened for candidate genes. Five rare TRPM4 genetic variants were identified and investigated. The variants were expressed heterologously in HEK293 cells. Two of the variants, A432T and A432T/G582S, showed decreased expression of the protein at the cell membrane; inversely, the G582S variant showed increased expression. Further functional characterization of these variants using whole‐cell patch‐clamp configuration showed a loss of function and a gain of function, respectively. We hypothesized that the observed decrease in expression was caused by a folding and trafficking defect. This was supported by the observation that incubation of these variants at lower temperature partially rescued their expression and function. Previous studies have suggested that altered SUMOylation of TRPM4 may cause a gain of function; however, we did not find any evidence that supports SUMOylation as being directly involved for the gain‐of‐function variant. Conclusions: This study underpins the role of TRPM4 in the cardiac conduction system. The loss‐of‐function variants A432T/G582S found in 2 unrelated patients with atrioventricular block are most likely caused by misfolding‐dependent altered trafficking. The ability to rescue this variant with lower temperature may provide a novel use of pharmacological chaperones in treatment strategies.